2010
DOI: 10.1124/jpet.110.173278
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Stromal Cell-Derived Cyclooxygenase-2 Metabolite Prostaglandin E2 on the Proliferation of Colon Cancer Cells

Abstract: It is well known that tumor-surrounding stromal tissues support tumor development through secreting soluble factors such as various cytokines, chemokines, and growth factors. It has also been suggested that tumor-associated fibroblast and immune cells have a high expression of cyclooxygenase-2 (COX-2) and produce and secrete several prostaglandins (PGs) to adjacent cancer tissues. From these findings, we assumed that COX-2 inhibition might have an anticancer effect on cancer cells even without COX-2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Considering that angiogenesis takes place within PCCS, and proliferation as well as stem cell markers might be related to that [15][16], [29][30], we investigated the potential connection between these events under FLX treatment. CD133-positive cells expressing VEGF were found within PCCS in mice subjected either to MNNG or MNNG+FLX treatments (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that angiogenesis takes place within PCCS, and proliferation as well as stem cell markers might be related to that [15][16], [29][30], we investigated the potential connection between these events under FLX treatment. CD133-positive cells expressing VEGF were found within PCCS in mice subjected either to MNNG or MNNG+FLX treatments (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor stroma constitutes 60–90% of the colon tumor mass [14], and PCCS surrounding the cryptal bottom has been reported to initiate certain steps in colon tumor development, such as increased proliferation, microvessel formation, VEGF-synthesis, regulation of self-renewal and differentiation of intestinal cells [15][18]. ACFs are considered a suitable experimental model for studying early stages of colon cancer formation, mainly due to their close resemblance with the development of cancer in rodents and humans [17], [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a stromal cell system, COX-2 transfected stromal cells significantly increased colorectal tumor cell proliferation as well as VEGF synthesis. This effect was partially inhibited by EP4 antagonism [105]. A second critical mechanism underlying the proliferative effects of PGE 2 was recently demonstrated by showing that the pro-metastatic protein, human enhancer of filamentation 1 (HEF1; NEDD9), links PGE 2 to the cell-cycle machinery in colon cancer cells [106].…”
Section: Eicosanoid Expression and Cell Proliferation In Colorectal Cmentioning
confidence: 98%
“…It has been reported that AA-derived prostaglandins enhance cell proliferation in colon cancer cells ( 26 ). Because intestinal PGE 2 was decreased in Fads1 null mice (described above), we examined the level of cell proliferation in mouse colon crypts.…”
Section: Fads1 Deletion Decreases Colonic Cell Proliferationmentioning
confidence: 99%